Prevalence of drug-related problems in self-medication in Danish community pharmacies - Bente Frøkjær; Tina Bolvig; Nina Griese; Hanne Herborg; Charlotte Rossing (University of Minnesota Libraries Publishing, 2012)
Background: Drug-related problems are known to be a major problem associated with pharmacotherapy. A broad range of studies, mainly in the area of prescription-only medicines, supports this fact. Only a few studies have evaluated drug-related problems with over-the-counter medicine and the role of community pharmacies in this. Purpose: To quantify drug-related problems in self-medication (use of over-the-counter medicine) identified by community pharmacies in Denmark and to document the interventions by pharmacy staff in relation to the identified drug-related problems. Method: A descriptive study mapping drug-related problems in self-medication registered at the counter at a selected number of Danish community pharmacies. Results: Data for 3,868 consecutive customers with requests for over-the-counter (OTC) medicines were registered at 39 community pharmacies. The pharmacies registered a total number of 4,324 OTC medicines requests, illustrating that a customer requested 1.1 OTC medicines on average. Drug-related problems (DRPs) were identified for 813 customers, equivalent to DRPs for 21.0 % of all customers, presenting symptoms or requesting OTC medicines, and for 20 % of all over-the-counter medicines requests. 1,239 DRPs were registered, corresponding to an average of 1.5 DRPs per customer requesting OTC medicines. Community pharmacies estimated that they solved or partly solved 76.2 % of the detected DRPs; 73 % were solved without involving a general practitioner. Conclusions: DRPs were identified for 21.0 % of the pharmacy customers presenting a symptom or asking for an OTC medicine. The community pharmacy counselled the customers with DRPs more thoroughly than other customers by giving 2.4 pieces of professional advice, compared to an average of 2.1 to customers in general. It is not possible to determine the magnitude of the safety risk involved. Based on the most frequent categories of DRPs, there were risks of insufficient effect, unintended effects and, to a lesser extent, inappropriate self-medication.   Type: Original Research